How Do Bi+ Mothers' Talk with Their Children about (Their) Bisexuality+?. Issue 4 (8th August 2022) - Davenport-Pleasance, Ellen; Imrie, Susan
Abstract: Whereas a great deal is known about lesbian/gay parent families, much less is known about bi+ mother families, especially relating to the ways bi+ mothers discuss their bisexuality+ with their children. This article explores conversations about bisexuality+ and queer socialization in bi+ mother families. Semi-structured interviews were conducted online with 29 bi+ mothers, with each interview lasting one to two hours. Mothers were asked about whether they had discussed their bisexuality+ with their child(ren), their reasoning for wanting to discuss their sexuality with their child(ren), how they broached the topic, whether they used any resources, and how the child(ren) reacted. Interviews were analyzed using thematic analysis, informed by prior literature on cultural socialization and disclosure. Analysis revealed that bi+ mothers adopted various strategies and approaches to discussing their bisexuality+ with their children, which were often child-focused and based on a consideration of children's developmental abilities. Bi+ mothers also engaged in queer socialization practices, such as cultural socialization, preparation for bias, and mainstream queer socialization. The theoretical and empirical implications of this research are discussed, as well as the practical implications, such as providing support to bi+ mother families. Directions for future research are also identified.